MAKING A NOTARY DEED THAT PROVIDES LEGAL CERTAINTY - Hustam Husain; Kahar Lahae; Marwah (Awang Long Law Review, 2022)
The purpose of this study is to analyze and understand the level of obedience of a Notary in making a Notary deed. This type of research is empirical legal research. Empirical legal research is oriented to primary data (research results in the field). Empirical legal research is an approach carried out by field research by seeing and observing what is happening in the field, and the application of these regulations in practice in society. All data obtained in the study, both primary data and secondary data, were analyzed using qualitative analysis techniques. After that it is described, by examining the existing problems, describing, describing, and explaining the problems related to this research. The use of this descriptive method is intended to obtain a good, clear picture and can provide as detailed data as possible about the object under study, in this case, to describe how legal certainty and protection is for the community through the making of a Notary deed with legal certainty. Based on these results, a conclusion is drawn which is the answer to the problems formulated in this study and suggestions that aim to provide input for further improvement. The results of this study indicate that in carrying out the duties of office, there are still Notaries who do not carry out the provisions as stipulated in the UUJN, the Notary Code of Ethics, and other laws and regulations. This is because the Notary in carrying out his position is still influenced by internal and external factors, so that due to his disobedience to the procedures and procedures for making the deed results in the degradation of the deed made or produced by the Notary.